Forests for markets: can a market ban on soybeans deter deforestation in the legal Amazon? - Peixoto, Pedro Henrique Guimarães Pinto (2017)
This work aims to evaluate the Soy Moratorium, an industry led initiative to curb deforestation in the Amazon Biome. Under this agreement, all signatories commit to not buy soybeans produced in lands deforested after July 2006. There is no effective evaluation of this program and the literature in economics have not addressed the question of whether a market ban could reduce deforestation. My main specification is a triple-difference estimate and I find that, unlike previous evaluations, the moratorium had no effect to reduce deforestation.